Confronting the global obesity epidemic: investigating the role and underlying mechanisms of vitamin D in metabolic syndrome management - Liang, Zihui; Wang, Ziliang; Liu, Xueyong; He, Yu (Frontiers in Nutrition, 2024)
The escalating prevalence of MetS, driven by global obesity trends, underscores the urgent need for innovative therapeutic strategies. To gain a deeper understanding of the therapeutic potential of vitamin D in addressing MetS, we embarked on a targeted literature review that thoroughly examines the scientific underpinnings and pivotal discoveries derived from pertinent studies, aiming to unravel the intricate mechanisms through which vitamin D exerts its effects on MetS and its components. This article explores the multifunctional role of vitamin D in the management of MetS, focusing on its regulatory effects on insulin sensitivity, lipid metabolism, inflammation, and immune response.Through an extensive review of current research, we unveil the complex mechanisms by which vitamin D influences MetS components, highlighting its potential as a therapeutic agent. Our analysis reveals that vitamin D's efficacy extends beyond bone health to include significant impacts on cellular and molecular pathways critical to MetS. We advocate for further research to optimize vitamin D supplementation as a component of precision medicine for MetS, considering the safety concerns related to dosage and long-term use.